Measuring Software Quality in Use: State-ofthe-Art and Research Challenges - Bong, Chih How; Issa, Atoum (Universiti Malaysia Sarawak (UNIMAS), 2015)
Software quality in use comprises quality from the user’s perspective. It has gained its importance in e-government applications, mobile-based applications, embedded systems, and even business process development. Users’ decisions on software acquisitions are often ad hoc or based on preference due to difficulty in quantitatively measuring software quality in use. But, why is quality-in-use measurement difficult? Although there are many software quality models, to the authors’ knowledge no works survey the challenges related to software quality-in-use measurement. This article has two main contributions: 1) it identifies and explains major issues and challenges in measuring software quality in use in the context of the ISO SQuaRE series and related software quality models and highlights open research areas; and 2) it sheds light on a research direction that can be used to predict software quality in use. In short, the qualityin- use measurement issues are related to the complexity of the current standard models and the limitations and incompleteness of the customized software quality models. A sentiment analysis of software reviews is proposed to deal with these issues.